Predictors of intention not to use cannabis among young adults who attend adult education centers. (April 2013) - Gagnon, Hélène; Côté, José; April, Nicole; Julien, Anne-Sophie; Tessier, Sébastien
<x xml:space="preserve">Abstract</x> Cannabis use among young people and the consequences of such use on their health and their school attainment concern a number of health care providers, teachers, and parents. This study attempts to document cannabis use among youth attending adult education centers in the province of Quebec, Canada, and to identify factors associated with their intention not to use cannabis in the next month. An extended version of the theory of planned behavior was applied. A total of 260 young adults, randomly recruited in nine adult education centers, completed the questionnaire. Of these, 133 reported having used cannabis in the past year. In this sub-sample more than one-third (30.3%) use cannabis every day. The intention prediction model demonstrated that perceived behavioral control and attitude are two determinant variables. The intention not to use cannabis is also related to anticipated regret and frequency of use. The results of this study revealed several options for helping young people not to use cannabis during their school career.